Equal cancer treatment regardless of education level and family support? A qualitative study of oncologists' decision-making. Issue 4 (24th August 2012) - Cavalli-Björkman, Nina; Glimelius, Bengt; Strang, Peter
Abstract : Objective: Treatment gradients by socioeconomic status have been observed within cancer care in several countries. The objective of this study was to explore whether patients' educational level and social network influence oncologists' clinical decision-making. Design: Semi-structured interviews on factors considered when deciding on treatment for cancer patients. Interviews were transcribed and analysed using inductive qualitative content analysis. Setting: Oncologists in Swedish university- and non-university hospitals were interviewed in their respective places of work. Participants: Twenty Swedish clinical oncologists selected through maximum-variation sampling. Primary and secondary outcome measures: Elements which influence oncologists' decision-making process were explored with focus on educational level and patients' social support systems. Results: Oncologists consciously used less combination chemotherapy for patients living alone, fearing treatment toxicity. Highly educated patients were considered as well-read, demanding and sometimes difficult to reason with. Patients with higher education, those very keen to have treatment and persuasive relatives were considered as challenges for the oncologist. Having large groups of relatives in a room made doctors feel outnumbered. A desire to please patients and relatives was posed as the main reason for giving in to patients' demands, even when this resulted in treatment with limited efficacy. Conclusions: Oncologists tailor treatment for patients living alone to avoid harmful side-effects. Many find patients' demands difficult to handle and this may result in strong socioeconomic groups being over-treated.